Drones may be used to save lives in out of hospital cardiac arrest due to drowning. (May 2017) - Claesson, A.; Svensson, L.; Nordberg, P.; Ringh, M.; Rosenqvist, M.; Djarv, T.; Samuelsson, J.; Hernborg, O.; Dahlbom, P.; Jansson, A.; Hollenberg, J.
Abstract: Background: Drowning leading to out-of-hospital cardiac arrest (OHCA) and death is a major public health concern. Submersion with duration of less than 10 min is associated with favorable neurological outcome and nearby bystanders play a considerable role in rescue and resuscitation. Drones can provide a visual overview of an accident scene, their potential as lifesaving tools in drowning has not been evaluated. Aim: The aim of this simulation study was to evaluate the efficiency of a drone for providing earlier location of a submerged possible drowning victim in comparison with standard procedure. Method: This randomized simulation study used a submerged manikin placed in a shallow (<2 m) 100 × 100-m area at Tylösand beach, Sweden. A search party of 14 surf-lifeguards (control) was compared to a drone transmitting video to a tablet (intervention). Time from start to contact with the manikin was the primary endpoint. Results: Twenty searches were performed in total, 10 for each group. The median time from start to contact with the manikin was 4:34 min (IQR 2:56–7:48) for the search party (control) and 0:47 min (IQR 0:38–0:58) for the drone-system (intervention) respectively (p < 0.001). The median time saved by using the drone was 3:38 min (IQR 2:02–6:38). Conclusion: A drone transmitting live video to a tablet is feasible, time saving in comparison to traditional search parties and may be used for providing earlier location of submerged victims at a beach. Drone search can possibly contribute to earlier onset of CPR in drowning victims.